Development of injectable hydrogels based on human amniotic membrane and polyethyleneglycol-modified nanosilicates for tissue engineering applications. (5th October 2022) - Kafili, Golara; Tamjid, Elnaz; Niknejad, Hassan; Simchi, Abdolreza
Graphical abstract: Highlights: Nanocomposite hydrogels based on human amniotic membrane provide thermosensitivity to physiologic temperature. Hydrogels offer shear-thinning rheological behavior favorable for in-situ injection applications. Laponite nanoparticles aggregate in the amniotic membrane-derived hydrogels due to the presence of charged ions in the solution. The hydrophobic nature of laponite leads to its alternative laminate arrangement between collagen fibers. Amine-terminated PEG modification of laponite can improve their dispersion in amniotic membrane-derived hydrogel. Abstract: Recently, decellularized amniotic membrane-derived hydrogels (DAMHs) have received significant attention for wound care, ocular surface reconstruction, and chondral healing. Despite the advantages of DAMHs for tissue engineering (TE), the loss of structural components during the decellularization process mitigates their mechanical strength and thus limits their practical application. Herein, we present a method for the surface modification of two-dimensional nanosilicates (laponite) as a rheological modifier to tailor the properties of DAMHs. Results show that after introducing nanosilicates, severe aggregation of the nanoparticles occurs, owing to the shielding effect of ions on the surface and edges of laponite. Loose interactions between the hydrophobic nanosilicate tactoids and hydrophilic polymer form laminated clay clusters surrounded by collagen fibers. At a high concentration of laponite (1:1 w/w), liquid-solid phase separation may also occur. A decreased storage modulus (up to 80 %), swelling ratio (up to 50 %), and gelation rate (up to 16 %) are thus attained. Electrosteric stabilization of the nanosilicates with amine-terminated polyethyleneglycol (AT-PEG) prevents aggregation of the nanosilicate in the hydrogel matrix and provides uniform distribution. As a result, most of the impaired physicomechanical properties are resolved.  In vitro  cell studies also determine that the AT-PEG modified nanosilicate-DAMHs exhibit higher cell viability and cell adhesion. The results of this research can pave the way toward developing injectable DAMHs with improved properties for TE.